Recycling of Lithium-Ion Batteries The LithoRec Way - Kwade, Arno.; Diekmann, Jan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book addresses recycling technologies for many of the valuable and scarce materials from spent lithium-ion batteries. A successful transition to electric mobility will result in large volumes of these.  The book discusses engineering issues in the entire process chain from disassembly over mechanical conditioning to chemical treatment. A framework for environmental and economic evaluation is presented and recommendations for researchers as well as for potential operators are derived.
Foreword -- Background -- The LithoRec process -- Potential dangers during the handling of lithium-ion batteries -- Overdischarging lithium-ion batteries -- Disassembly planning and assessment of automation potentials for lithium-ion batteries -- Safe, flexible and productive human-robot-collaboration for disassembly of lithium-ion batteries -- Crushing of battery modules and cells -- Separation of the electrolyte - Thermal drying -- Separation of the electrolyte - Solvent extraction -- Electrolyte extraction - sub and supercritical CO2 -- Off gas cleaning by adsorption -- Material separation -- Hydrometallurgical processing and thermal treatment of active materials.- Realization in a demonstration plant -- Economic assessment of the LithoRec process -- Environmental aspects of the recycling of lithium-ion traction batteries.
Keywords: Manufactures; Refuse and refuse disposal; Electrochemistry; Electric power production; Machines, Tools, Processes; Waste Management/Waste Technology; Electrochemistry; Electrical Power Engineering; Mechanical Power Engineering